Hubungan Relational Capital dengan Kinerja Perusahaan: Entrepreneurial Orientation sebagai Variabel Intervening - Nasir Nasir (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2020)
The purpose of this article is to conceptualizing the relationship between Relational Capital to corporate performance through Entrepreneurship Orientation (EO) as an intervening variable. This study is conceptual paper (Non Empirical) who tried to examine the conceptual relationship antaraRC and performance of the company, where the concept of EO as an intervening variable. The reconstruction of concepts offered from this study can be continued in empirical research so that it is expected to be able to contribute in adding various views about EO which are part of management strategies.